2018
DOI: 10.1080/08916934.2018.1519027
|View full text |Cite
|
Sign up to set email alerts
|

Childhood thyroid autoimmunity and relation to islet autoantibodies in children at risk for type 1 diabetes in the diabetes prediction in skåne (DiPiS) study

Abstract: Larsson & the DiPiS study Group (2018) Childhood thyroid autoimmunity and relation to islet autoantibodies in children at risk for type 1 diabetes in the diabetes prediction in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 48 publications
3
13
0
Order By: Relevance
“…In our study, we found vital correspondence between the presence of GADA antibodies and both clinically manifested thyroid AD and asymptomatic thyroid autoimmunity. Our results are consistent with previously published data (39,43). Glutamic acid decarboxylase antibodies are found in ∼70-80% of patients who suffer from T1DM, long before the onset of clinical symptoms, and they remain positive over a long time after.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, we found vital correspondence between the presence of GADA antibodies and both clinically manifested thyroid AD and asymptomatic thyroid autoimmunity. Our results are consistent with previously published data (39,43). Glutamic acid decarboxylase antibodies are found in ∼70-80% of patients who suffer from T1DM, long before the onset of clinical symptoms, and they remain positive over a long time after.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with existing studies that notice thyroid autoimmunity more often in girls (33,39) and increase by 4.6% in prevalence of hypothyroidism (including subclinical cases) for every 10-year increase of age in T1D and with diabetes duration (15). These findings correlate with overall trends of thyroid autoimmunity incidence in other countries (39,40) and also in Poland (41). Contrary to our findings, the meta-analysis based on 14 studies shows that the risk of thyroid dysfunction is much higher in children in comparison to adults (42).…”
Section: Discussionsupporting
confidence: 93%
“… 20 Furthermore, a higher proportion of patients with T1DM positive for pancreatic islet beta-cell antibodies, insulin antibodies, and antiglutamic acid decarboxylase antibodies (GADAbs), which are often used for the diagnosis of T1DM, have been found to be positive for TPOAb. 5 , 21 27 Therefore, it is considered that AITD is the most prevalent T1DM-related autoimmune disease, whereas LADA is an independent risk factor for the development of AITD. 5 , 6 , 8 , 18 , 28 32 …”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these findings indicate that Chinese T1DM patients are also prone to other organ-specific autoimmune diseases, presumably related to the expansion of antibody recognition epitopes among different antigen molecules. Although previous studies have found that patients positive for IA-2A are at higher risk of thyroid dysfunction [26], there have been no reports that IA-2A-positive T1DM patients are more likely to be positive for thyroid antibodies. We found that patients positive for GADA or IA-2A were more likely to exhibit positivity for TPOA or TGA, suggesting that those patients are prone to develop comorbid thyroid autoimmune diseases.…”
Section: Discussionmentioning
confidence: 90%